TINJAUAN PERENCANAAN STRUKTUR BANGUNAN GEDUNG FLAT SATBRIMOB POLDA DI KABUPATEN KUBU RAYA - Wahyudi, Ega; Rosanti, Indah; Ariyansyah, Rona (RETENSI, 2020)
Along with the times, the planned building will provide Life Safety performance. Where the planned building may be damaged, but the structure must not collapse so that there are no fatalities, both in earthquake-prone and non-earthquake-prone areas.The building is designed using the Intermediate Moment Bearer Frame System (SRPMM). Designed to be strong against several load combinations such as dead load, live load, wind load, and earthquake load. he results of the structural analysis use the ETABS and SAP 2000 version 14 software to determine the internal forces acting on the structure, and are then used to calculate the reinforcement design stage and check the cross-sectional capacity of the structure.The process of reviewing the planning of the building structure planning for the Flat Sat Brimob Polda building in Kubu Raya Regency includes analyzing the roof structure, floor plate structure, beam structure, column structure and foundation structures.Based on the results of the analysis of calculations that have been carried out, it was found that the roof structure used mild steel C-75x45x15x1, 6 mm. Floor plate structure with a thickness of 150 mm.The main beam structure with dimensions (300 x 600) mm, the joist with dimensions (250 x 500) mm, ring beam 1 with dimensions (200 x 400) mm, 2 beam rings with dimensions (150 x 300) mm. There are 2 types of column structure, namely K1 and K2, in the K1 column the largest dimensions are 700x700 mm, for column K2 the largest dimension is 400x500 mm. The foundation structure used is a pile with a diameter of 400 mm, a depth of 24 m.